2017
DOI: 10.1021/acs.jpclett.7b01426
|View full text |Cite
|
Sign up to set email alerts
|

Strong Dependence of Quantum-Dot Delayed Luminescence on Excitation Pulse Width

Abstract: Delayed luminescence involving charge-carrier trapping and detrapping has recently been identified as a widespread and possibly universal phenomenon in colloidal quantum dots. Its near-power-law decay suggests a relationship with blinking. Here, using colloidal CuInS 2 and CdSe quantum dots as model systems, we show that short (ns) excitation pulses yield less delayed luminescence intensity and faster delayed luminescence decay than observed with long (ms) square-wave excitation pulses. Increasing the excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…The wide range of time scales involved in trap-related phenomena such as spectral diffusion (ns–s), ,, delayed emission (ns–ms), or blinking (μs–s), the broadly distributed electrochemical response, and the existence of an entirely nonemissive ( i . e ., “dark”) fraction of NCs all suggest a strong heterogeneity in trap properties.…”
mentioning
confidence: 99%
“…The wide range of time scales involved in trap-related phenomena such as spectral diffusion (ns–s), ,, delayed emission (ns–ms), or blinking (μs–s), the broadly distributed electrochemical response, and the existence of an entirely nonemissive ( i . e ., “dark”) fraction of NCs all suggest a strong heterogeneity in trap properties.…”
mentioning
confidence: 99%
“…Nevertheless, some of their key fundamental properties remain poorly understood. For example, while the excited state of a QD usually lives no longer than a few tens of nanoseconds before it decays by emitting a photon, sometimes emission takes orders of magnitude longer. This slow emissionor “delayed emission”is responsible for on the order of 10% of the fluorescence from various types of QDs, including CdSe/CdS/CdZnS/ZnS core/multishells, Cu-doped CdSe, CuInS 2 , and lead–halide perovskites . It is typically ascribed to trapping and detrapping of excited charge carriers, which renders the excited state of the QD temporarily nonemissive.…”
mentioning
confidence: 99%
“…It was recently shown that, upon pulsed excitation of an ensemble of separated QDs, spontaneous emission on nanosecond time scales is followed by strongly delayed emission at the same photon energies up to milliseconds after photoexcitation. The amplitude of delayed emission in a photoluminescence (PL) decay experiment is often low, and its existence has been overlooked. However, the time-integrated delayed emission accounts for more than 10% of the overall emission for many types of QDs. The current understanding is that the recombination of an electron–hole pair is delayed because one (or both) charge carrier is temporarily stored in a trap state. The original exciton state is restored after some time by release of the trapped charge carrier.…”
mentioning
confidence: 99%
“…The decay statistics change to power-law (straight line on a double-logarithmic scale) after the intensity drops to a few percent of the initial intensity. This power-law emission has been termed “delayed emission” and attributed to emission after temporary exciton storage by reversible trapping of charge carriers. , The power-law statistics (intensity proportional to t –α ) reflect the wide distribution of the release times of the charge carriers from the trap states. Previous studies have demonstrated that the state with a trapped charge carrier can persist for up to milliseconds before the carrier is released, , the exciton state is restored, and a delayed photon is emitted.…”
mentioning
confidence: 99%
See 1 more Smart Citation